Biological Properties and Genetic Characteristics of Francisella tularensis Strains Isolated in the Territory of the Rostov Region in 2020 - M. V. Tsimbalistova; V. M. Sorokin; N. V. Aronova; A. S. Anisimova; N. L. Pichurina; N. I. Pasyukova; N. A. Selyanskaya; S. O. Vodop’yanov; A. S. Vodop’yanov; R. V. Pisanov; N. V. Pavlovich; E. V. Kovalev; et al. (Canadian Journal of Fisheries and Aquatic Sciences, 2021)
Objective of the study was to investigate biological properties and genetic characteristics of tularemia agent strains isolated from natural foci of the Rostov Region in 2020.Materials and methods. Field material from natural foci of the Rostov Region was examined by serological, bacteriological, biological, and molecular-genetic methods. Cultural-morphological, biochemical, antigenic and pathogenic properties of isolated cultures were studied. Protein profles were obtained through MALDI-TOF MS using mass spectrometer Autoﬂex speed III Bruker Daltonics and Flex Control of Biotyper software. The genetic characteristics of the strains were determined by VNTR and INDEL typing and SNP analysis.Results and discussion. Six strains of tularemia pathogen were isolated from mouse-like rodents using biological method. The investigation of their biological features and data of PCR analysis and INDEL typing with canonical markers showed that all strains are typical representatives of the Francisella tularensis subsp. holarctica biovar EryR. VNTR typing by six genetic loci revealed that all strains belong to four individual genotypes. The strain isolated in 2020 in the Salsky district was identical to the strain which was isolated in the same area in 1989. Based on the whole genome sequencing of two strains, we established that they are closest to the cultures isolated in Turkey (2009, 2012) and Khanty-Mansiysk (2013) by the studied set of SNP markers. Thus, we found that both identical (or closely related) clones of the tularemia agent and new strains with unique genotypes which previously were not described for the Rostov Region can circulate in natural foci of this region for a long period of time. Цель работы – изучение биологических свойств и генетических характеристик штаммов возбудителя туляремии, изолированных в природных очагах Ростовской области в 2020 г.Материалы и методы. Полевой материал исследовали серологическим, бактериологическим, биологическим и молекулярно-генетическими методами. Получение белковых ...